Teknik Adaptive pada Modulasi Delta - Djadjat Sudaradjat (Paradigma, 2019)
DM (Delta Modulation) is one of the waveform coding methods that converts analog waveforms into digital waveforms, by encoding binary numbers 1 when analog waveforms rise, and encodes binary numbers 0 when analog waveforms drop, and if analog waveforms are flat will be encoded binary numbers 1 and 0 alternately. So that the row of binary numbers 1 and 0 will show the fluctuation of the analog signal form. Problems faced in Delta Modulation when the ups and downs of analog waveforms are too steep or too tilted so that analog waveform changes cannot be followed, there will be slope overload noise, which causes SNR (Signal to Noise Ratio) to shrink because it is unable follow the analog wave changes which are too high to produce a large noise. For this reason, Adaptive techniques are made, so that excess can be avoided, thereby reducing the Noise and SNR expected to be obtained. ADM (Adaptive Delta Modulation) reduces load tilt errors, and seeks to increase dynamic range. Adaptive algorithms adjust the step size (from various step sizes) to the signal power level and thus increase the dynamic range of the coding system. This paper discusses Delta Modulation techniques for increasing SNR with ADM techniques, as well as performance comparisons between DM and ADM.